SARS-CoV-2 Viability on 16 Common Indoor Surface Finish Materials. (July 2021) - Ronca, Shannon E.; Sturdivant, Rodney X.; Barr, Kelli L.; Harris, Debra
Aim: This study investigated the stability of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on 16 common environmental surface materials. Background: SARS-CoV-2 is the causative agent of severe coronavirus disease, a significant public health concern that quickly led to a pandemic. Contamination of environmental surface materials is of concern, with previous studies identifying long-term detection of infectious particles on surfaces. These contaminated surfaces create an increased risk for contact transmission. Methods: Surface materials were inoculated with 10, 000 plaque forming units and samples were collected 4, 8, 12, 24, 30, 48, and 168 hours post infection (hpi). Viral titers were determined for each sample and time point using plaque assays. Nonparametric modeling utilized the Turnbull algorithm for interval-censored data. Maximum likelihood estimates for the survival curve were calculated. Parametric proportional hazards regression models for interval censored data were used to explore survival time across the surface materials. Results: There was a sharp decline in recoverable virus after 4 hpi for all tested surfaces. By 12 hpi, infectious SARS-CoV-2 was recoverable from only four surfaces; and by 30 hr, the virus was recoverable from only one surface. There were differences in survival curves based on the materials although some groups of materials are similar, both statistically and practically. Conclusions: While very low amounts of infectious SARS-CoV-2 are recoverable over time, there remains a risk of viral transmission by surface contamination in indoor environments. Individuals and institutions must follow appropriate procedures to decontaminate indoor environment and increase diligence for hand hygiene and personal protective equipment.